1999
DOI: 10.1046/j.1440-1754.1999.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress experienced by mothers of Malaysian children with mental retardation

Abstract: A large proportion of mothers of children with mental retardation experienced substantial parenting stress, especially Chinese and unemployed mothers, and this warrants appropriate intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 14 publications
(44 reference statements)
1
45
0
1
Order By: Relevance
“…with studies in other Chinese cultures, these have reported high levels of stress among mothers (Ong, Chandran, & Peng, 1999) and maternal ill-health (Huang, 1999). Chinese mothers are reputed to use a variety of coping styles (Cheng & Tang, 1993), which broadly replicate those proposed by Lazarus and Folkman (1984) in their pioneering research in this area.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…with studies in other Chinese cultures, these have reported high levels of stress among mothers (Ong, Chandran, & Peng, 1999) and maternal ill-health (Huang, 1999). Chinese mothers are reputed to use a variety of coping styles (Cheng & Tang, 1993), which broadly replicate those proposed by Lazarus and Folkman (1984) in their pioneering research in this area.…”
Section: Introductionmentioning
confidence: 77%
“…But when this is allied with pressures on preserving harmony, this can create additional strains on parents, and mothers especially. Indeed there is some limited evidence that stresses are greater among Chinese mothers compared with those in other cultures (Ong, Chandran, & Peng, 1999). Poor communication can also lead to misunderstandings among family members and a lack of agreement on the plan of care (McLaughlin & Braun, 1998).…”
Section: Taiwanese Issuesmentioning
confidence: 99%
“…In Malaysia, however, this research is more limited. Noralina, Nur Saadah, Siti Hajar, and Fatimah (2010), Othman (2004), and Ong, Chandran, and Peng (1999) covered some components of informal caregiving experiences of chronically ill and disabled children in Malaysia. For example, Othman examined the role of parental overprotection and diseaserelated variables in exacerbating psychological problems of children suffering from chronic illness.…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of parenting stress were noted among Malaysian mothers of children with cerebral palsy and mental retardation compared with controls, and this was mediated by ethnicity, socio-economic status, care-giving burden and child behaviour. 10,11 Although cerebral palsy and mental retardation result in chronic disability, some of the longterm problems outlined above are unique to spina bifida. Hence, the purpose of this study was to determine factors associated with parenting stress among mothers of children with spina bifida.…”
Section: Introductionmentioning
confidence: 99%